Pembangunan Sistem Aplikasi Penyewaan pada DO-RENT berbasis Web (Studi Kasus: DO-RENT Malang) - Siti Alfina Putri Said; Bayu Priyambadha; Faizatul Amalia (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
Rental is an agreement through payment services for use of an item or property temporarily by another party or other person. Nowadays, the rental business is various, one of them is outbound, mountaineering, and communication tools rental. Do-Rent is one of rental business In Malang. In this digital era, Do-Rent wants to expand the business by using the website due to high demand day by day. Do-Rent Malang still uses conventional procedure, so that the clients from Malang and outside Malang have to come to the offline store for knowing the available tools. As the solution, a website-based application is carried out that facilitates the clients for booking or renting, both in the city and outside the city. From this case, the process of engineering needs is carried out and produces 19 functional needed and 1 non-functional needed. Furthermore, architecture planning, data planning, component planning, and interface planning are also carried out that will become a reference when doing the implementation of code program and interface. This system using unit testing, validation testing, and compatibility testing. From the system, the results of the test case are 100% valid and compatibility system testing runs well on 8 browsers.